2019
DOI: 10.33371/ijoc.v13i3.670
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA Expression Profile of PD-1 and PD-L1 in Peripheral Blood of Colorectal Cancer Patients

Abstract: Background: Immunotherapy using immune checkpoint inhibitors has currently emerged as an effective treatment for a subset of colorectal cancer (CRC) patients. The roles of PD-1 and PD-L1 expression levels in peripheral blood to predict patient’s response to immune checkpoint inhibitors are not well established. Therefore, we analyzed PD-1 and PD-L1 mRNA expression levels of peripheral blood in Indonesian CRC patients and explored the association with the clinicopathological features.Methods: Peripheral blood o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A contradicting result to what we have found, Ajoedi et al who documented that PD-1 mRNA expression decreased in peripheral blood of CRC patients compared to healthy individuals. PD-1 expression tends to be low in CRC with advanced stages [39].…”
Section: Discussionmentioning
confidence: 95%
“…A contradicting result to what we have found, Ajoedi et al who documented that PD-1 mRNA expression decreased in peripheral blood of CRC patients compared to healthy individuals. PD-1 expression tends to be low in CRC with advanced stages [39].…”
Section: Discussionmentioning
confidence: 95%
“…For instance, PD-L1 mRNA expression in platelet and exosomes also contribute to predicting the clinical response to immunotherapy ( 29 ), the measurement of PD-L1 mRNA expression in tumor tissue by RNA-seq is analytically and clinically in predicting the immune checkpoint inhibitor response ( 30 ), and blood expressed PD-L1 mRNA level was confirmed to be associated with anti–PD-1 response ( 12 14 ). Moreover, compared with the healthy controls, tissue PD-L1 mRNA expression decreased in patients with colorectal cancer ( 31 ) and could successfully discriminate the worse progression-free survival of those patients with colorectal cancer liver metastases who adopted neoadjuvant-treatment ( 32 ). However, some literature studies express the opposite view and reported that no statistically significant difference in the PD-L1 mRNA expression between responders and non-responders to immunotherapy was observed ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was classically used in the cDNA synthesis kit (Fermentas, Germany). According to the instructions of the manufacturer of the kit, five pairs of oligonucleotide primers for targets and endogenous genes were used and referenced [ 35 , 36 , 37 , 38 , 39 ], as illustrated in Table 1 .…”
Section: Methodsmentioning
confidence: 99%